Antimicrobial Activity of Striped Catfish (Pangasius hypophthalmus) Gelatin-Based Edible Film Incorporated with Betel Leaf (Piper betle L.) Extract as an Oral Freshener - Azlaini Yus Nasution; Athilya Putri Marundani; Nadya Putri Serawaidi (LPPM Universitas Abdurrab, 2025)
Innovation in the food industry continues to develop, particularly in the design of edible packaging materials (edible films). In addition to their packaging function, edible films have potential applications as oral freshening preparations capable of refreshing breath and reducing oral malodor. The development of such preparations can be combined with natural ingredients possessing biological activities, such as green betel leaf (Piper betle L.), which is known for its antibacterial and antifungal properties. This study aimed to evaluate the antimicrobial and antifungal activities of edible films based on striped catfish (Pangasius hypophthalmus) skin gelatin incorporated with green betel leaf extract. This research employed a laboratory-based experimental design, beginning with the extraction of gelatin from catfish skin, followed by the formulation of edible films containing betel leaf extract at concentrations of 0%, 1%, 2%, and 3%. Antimicrobial and antifungal activities were assessed using the disk diffusion method against Staphylococcus aureus, Streptococcus mutans, and Candida albicans.The results demonstrated that increasing the concentration of betel leaf extract enhanced the inhibition zones against the tested microorganisms. The highest inhibition zones against Staphylococcus aureus and Streptococcus mutans were observed at a 3% extract concentration, measuring 16.30 mm and 12.00 mm, respectively. Antifungal activity against Candida albicans showed relatively small but concentration-dependent increases in inhibition zones. Striped catfish skin gelatin–based edible films incorporated with green betel leaf extract show promising potential as antimicrobial oral freshening preparations.